Stereoscopic Imaging Technology: A Review of Patents and the Literature - Starks, Michael (International Journal of Virtual Reality, 1995)
This article contains comments on the nature of stereo perception as it relates to stereo video displays as well as a discussion of interfaces for stereo graphics and the interaction of stereo video and stereo graphics. A number of areas of interest are briefly reviewed and accompanied by extensive citations from the patent and technical literature. These include single camera (70 references) and dual camera (100 references) stereoscopy, compatible 3D recording and transmission (57 references), head mounted displays (85 references), field sequential stereo (285 references), and autostereoscopic systems including lenticular (64 references), parallax barrier (22 references), stereoptiplexer (17 references), integral imaging (24 references), direction selective mirrors, lenses or screens (26 references), volumetric displays (133 references), holovision (13 references), stereoendoscopy (14 references), and stereosculpting (15 references). Also discussed are interfaces for stereo graphics and the interaction of stereo video and stereo graphics.